Cytotoxic Taccalonolides and Withanolides from Tacca chantrieri - Ni, Gang; Yang, Han-Ze; Fu, Nai-Jie; Zhang, Lei-Lei; Wang, Ming-Chun; Chen, Jing; Zhang, Chun-Lei; Li, Yan; Chen, Xiao-Guang; Chen, Ruo-Yun; Yu, De-Quan (Planta Medica, 2015)
Six new taccalonolides, taccalonolides AT-AY (1–6), and two new withanolides, chantriolides D and E (7 and 8), together with ten known compounds (9–18), have been isolated from whole plants of Tacca chantrieri. The structures, including the absolute configurations of some of the compounds, were determined by spectroscopic and chemical methods. All compounds were evaluated for their in vitro cytotoxicity against five tumor cell lines. Compounds 9, 10, 13–15, and 17 exhibited cytotoxic activity, with IC50 values of 1.13–5.71 µM, while compound 7 showed selective cytotoxicity. The results indicated that taccalonolides with a six-membered lactone moiety located at C-15 and C-24 were devoid of cytotoxicity against five tumor cell lines (> 10 µM).
Keywords: Tacca chantrieri; Dioscoreaceae; taccalonolides; withanolides; cytotoxicity